Pengaruh Pengalaman Belanja Online, Gaya Hidup, dan Kualitas Produk Terhadap Keputusan Pembelian Skincare Npure di E-Commerce TikTok Shop - Annensi Perawati; Mauli Siagian (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This study aims to analyze the influence of online shopping experience, lifestyle, and product quality on purchasing decisions for Npure skincare products through the TikTok Shop e-commerce platform. The research method used is a quantitative approach with descriptive characteristics, which aims to systematically and objectively identify and measure causal relationships between variables. This study involved 204 respondents who are active TikTok Shop users and have experience purchasing Npure skincare products. The sampling technique was carried out using purposive sampling with certain criteria, and considering the Jacob Cohen approach to ensure the adequacy of the sample size. The data processing process was carried out through validity and reliability tests, classical assumption tests, regression analysis, and hypothesis testing to determine the magnitude of the influence of each independent variable on purchasing decisions. The results showed that online shopping experience contributed 29.7% of the influence on purchasing decisions, followed by consumer lifestyle with 29.0%, and product quality with 25.5%. Simultaneously, these three variables were able to explain 76.5% of the variation in purchasing decisions, as indicated by the coefficient of determination (R²), while the remainder was influenced by other factors outside the research model. Thus, it can be concluded that online shopping experience, lifestyle, and product quality partially or together have a significant influence on the decision to purchase Npure skincare on the TikTok Shop e-commerce.